Multidimensional effects of voice therapy in patients affected by unilateral vocal fold paralysis due to cancer - Barcelos,Camila Barbosa (2018)
Abstract Introduction: Patients with unilateral vocal fold paralysis may demonstrate different degrees of voice perturbation depending on the position of the paralyzed vocal fold. Understanding the effectiveness of voice therapy in this population may be an important coefficient to define the therapeutic approach. Objective: To evaluate the voice therapy effectiveness in the short, medium and long-term in patients with unilateral vocal fold paralysis and determine the risk factors for voice rehabilitation failure. Methods: Prospective study with 61 patients affected by unilateral vocal fold paralysis enrolled. Each subject had voice therapy with an experienced speech pathologist twice a week. A multidimensional assessment protocol was used pre-treatment and in three different times after voice treatment initiation: short-term (1-3 months), medium-term (4-6 months) and long-term (12 months); it included videoendoscopy, maximum phonation time, GRBASI scale, acoustic voice analysis and the portuguese version of the voice handicap index. Results: Multiple comparisons for GRBASI scale and VHI revealed statistically significant differences, except between medium and long term (p < 0.005). The data suggest that there is vocal improvement over time with stabilization results after 6 months (medium term). From the 28 patients with permanent unilateral vocal fold paralysis, 18 (69.2%) reached complete glottal closure following vocal therapy (p = 0.001). The logistic regression method indicated that the Jitter entered the final model as a risk factor for partial improvement. For every unit of increased Jitter, there was an increase of 0.1% (1.001) of the chance for partial improvement, which means an increase on no full improvement chance during rehabilitation. Conclusion: Vocal rehabilitation improves perceptual and acoustic voice parameters and voice handicap index, besides favor glottal closure in patients with unilateral vocal fold paralysis. The results were also permanent during the period of 1 year. The Jitter value, when elevated, is a risk factor for the voice therapy success.